2012
DOI: 10.1080/00103624.2012.644010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Exponential Fertilization Technique for Cultivation of Turfgrass during Early Growth Period

Abstract: The exponential fertilization method is based on the theory of supplying steady-state nutrition to young seedlings during the early, exponential growth stage. The objective of the research was to find the most effective method of fertilizing turfgrass during the early growth stage following seedling emergence. The field experiment was performed on turfgrass (tall fescue, Festuca arundinacea Schreb.) comparing a check (no fertilizer applied), two conventional fertilization techniques (equal additions and linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For example, with exponentially fertilized tall fescue seedlings where N application was designed to match the growth stage of plants, a steady state concentration of tissue N was reached at 44 to 46 g kg -1 during the 5-wk exponential growth period following germination (Li et al, 2012). Difference in physiological growth stage will have an effect on N requirements in turfgrass plants.…”
Section: Discussion Defining Cool-season Turfgrass Sufficiency Levelsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, with exponentially fertilized tall fescue seedlings where N application was designed to match the growth stage of plants, a steady state concentration of tissue N was reached at 44 to 46 g kg -1 during the 5-wk exponential growth period following germination (Li et al, 2012). Difference in physiological growth stage will have an effect on N requirements in turfgrass plants.…”
Section: Discussion Defining Cool-season Turfgrass Sufficiency Levelsmentioning
confidence: 99%
“…Difference in physiological growth stage will have an effect on N requirements in turfgrass plants. After the initial exponential growth period in turfgrass, the demand for N declines and less fertilizer N is required (Li et al, 2012), until the next demand period, which frequently occurs immediately after mowing if growth conditions are favorable. This is the period when demand for N is at its greatest, and these steady state concentrations of 44 to 46 g N kg -1 seemed to meet those demands.…”
Section: Discussion Defining Cool-season Turfgrass Sufficiency Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…et al [15] studied the effect of different fertilization methods on L. divaricata seedlings during growth, and the results showed that exponential fertilization is a valid option to reduce initial nutrient loss by leaching. Li et al [16] compared conventional fertilization with exponential fertilization to find the most effective method of fertilization during the early growth stage following seedling emergence. The results showed that turfgrass seedlings with the exponential fertilization technique exhibited significantly higher biomass accumulation, total nitrogen (N) concentration, and N content per seedling than those treated with the conventional fertilization method.…”
Section: Introductionmentioning
confidence: 99%